When things aren't going right, go left - Colagiovanni, Marc; Reynolds, Peter H. (Peter Hamilton), 1961- (New York : Orchard Books, 2023)
Reminding readers of their power to forge their own destinies, this deep and whimsical picture book creates an enduring message of strength and perseverance that is both universal and personal.
1.6
K-3
500L
Keywords: Conduct of life -- Juvenile fiction; Change -- Juvenile fiction; Self-esteem -- Juvenile fiction; Conduct of life -- Fiction; Change -- Fiction; Self-esteem -- Fiction